SITA JAMINAN DALAM KEPAILITAN - Sriti Hesti Astiti (Yuridika, 2014)
The law of bankruptcy basically has to pay more attention and give a proportionate legal protection between the interests of debtors to creditors, even also the interests of other credi-tors, who do not have a file in the bankruptcy process. Unfortunately, the legal protection for the other creditors which is regulated in Article 10 Law No. 37/2004 contains many weak-nesses and give many erroneous interpretation in the field of its structure, culture and the substance. Therefore, the legal enforcement and the conservatoir measures in bankruptcy law which has been intended to protect the legal interests of what we called “the other credi-tors” in the commercial court decision becomes unpredictable.Keyword : bankruptcy, other creditors, debtors.